Among the Laws of Arab Gulf States: Minimum Age of Marriage for Women in Omani Legislation - Al Mamari, Saleh Said; Al Aghbari, Fahad Yousuf; Al Shabibi, Zahira Hamood; Nizar Qeshta; Al Musalhi, Salim Ahmed; Al Rashdi, Ahmed Khalifa (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
This study addresses the issue of legal age of marriage for Omani women from human rights perspective, with a particular focus on the Omani legislation. It provides an analysis of relevant provisions within Omani law, particularly Articles 7 and 10 of the Personal Status Law, which stipulate the necessity of mental capacity and attainment of the age of majority for the validity of a marriage contract, while allowing judicial discretion in exceptional circumstances. The study further explores judicial interpretations by the Supreme Court, underscoring the fundamental principles of a woman’s consent and autonomy in the decision to marry. A comparative analysis with Gulf Cooperation Council (GCC) countries, including the United Arab Emirates, Saudi Arabia, Kuwait, Qatar, and Bahrain, is also conducted, highlighting disparities in the determination of the legal marriage age and the implications of the lack of official marriage registration on the protection of girls’ rights. The establishment of 18 as the legal marriage age in Omani law was not a reactive measure to international recommendations but rather preceded and aligns with them, drawing upon respected Islamic jurisprudential authorities such as Ibn Abbas and Imam Abu Hanifa. The Omani experience offers a balanced model that reconciles Sharia laws with the requirements of international conventions, without compromising core principles or yielding to external pressures. [Penelitian ini membahas usia minimum perkawinan bagi perempuan di Oman dari perspektif hak asasi manusia, dengan fokus pada peraturan perundang-undangan Oman. Kajian ini menyajikan analisis terhadap ketentuan-ketentuan yang relevan dalam hukum Oman, khususnya Pasal 7 dan Pasal 10 Undang-Undang Status Personal, yang mensyaratkan adanya kecakapan mental dan pencapaian usia dewasa sebagai syarat sahnya suatu akad perkawinan, sekaligus memberikan ruang bagi diskresi hakim dalam keadaan-keadaan tertentu yang bersifat luar biasa. Penelitian ini juga mengkaji interpretasi yudisial oleh Mahkamah Agung, dengan menekankan prinsip-prinsip fundamental mengenai persetujuan dan otonomi perempuan dalam pengambilan keputusan menikah. Selain itu, dilakukan pula analisis perbandingan dengan negara-negara anggota Gulf Cooperation Council (GCC), termasuk Uni Emirat Arab, Arab Saudi, Kuwait, Qatar, dan Bahrain, yang menyoroti perbedaan dalam penentuan usia legal perkawinan serta implikasi dari tidak adanya pencatatan perkawinan secara resmi terhadap perlindungan hak-hak anak perempuan. Temuan penelitian menunjukkan bahwa penetapan usia 18 tahun sebagai usia legal perkawinan dalam hukum Oman bukan merupakan respons reaktif terhadap rekomendasi internasional, melainkan telah mendahului dan sejalan dengan rekomendasi tersebut, dengan merujuk pada otoritas-otoritas fikih Islam yang dihormati seperti Ibnu Abbas dan Imam Abu Hanifah. Pengalaman Oman menawarkan sebuah model yang seimbang dalam merekonsiliasi hukum Syariah dengan tuntutan konvensi internasional, tanpa mengorbankan prinsip-prinsip dasar maupun tunduk pada tekanan eksternal.]